Clinically Oriented Anatomy Jilid 4,5,6 : the lower limb, the back, the upper limb - MOORE, Keith L. (WILLIAMS & WILKINS, 1900)
Clinically Oriented Anatomy Jilid 4,5,6 : the lower limb, the back, the upper limb